Epigenetic Clock Analysis in Children With Fetal Alcohol Spectrum Disorder. (22nd January 2021) - Okazaki, Satoshi; Otsuka, Ikuo; Shinko, Yutaka; Horai, Tadasu; Hirata, Takashi; Yamaki, Naruhisa; Sora, Ichiro; Hishimoto, Akitoyo
Abstract : Background: Fetal alcohol spectrum disorder (FASD) is characterized by severe clinical impairment, considerable social burden, and high mortality and morbidity, which are due to various malformations, sepsis, and cancer. As >50% of deaths from FASD occur during the first year of life, we hypothesized that there is the acceleration of biological aging in FASD. Several recent studies have established genome‐wide DNA methylation (DNAm) profiles as "epigenetic clocks" that can estimate biological aging, and FASD has been associated with differential DNAm patterns. Therefore, we tested this hypothesis using epigenetic clocks. Methods: We investigated 5 DNAm‐based measures of epigenetic age (HorvathAge, HannumAge, SkinBloodAge, PhenoAge, and GrimAge) and telomere length (DNAmTL) using 4 independent publicly available DNAm datasets; 2 datasets were derived from buccal epithelium, and the other 2 datasets were derived from peripheral blood. Results: Compared with controls, children with FASD exhibited an acceleration of GrimAge in 1 buccal and 2 blood datasets. No significant difference was found in other DNAm ages and DNAmTL. Meta‐analyses showed a significant acceleration of GrimAge in the blood samples but not in the buccal samples. Conclusions: This study provides novel evidence regarding accelerated epigenetic aging in children with FASD. Abstract : We hypothesized the acceleration of biological aging in fetal alcohol spectrum disorder (FASD), and performed analyses using epigenetic clocks that estimate biological aging based on genome‐wide DNA methylation profiles. We used four publicly‐available datasets. Children with FASD exhibited an acceleration of GrimAge, an epigenetic clock for mortality risk, in one buccal and two blood datasets. Meta‐analyses showed a significant acceleration of GrimAge in the blood datasets. This study provides novel evidence regarding accelerated epigenetic aging in children with FASD.